EFFECT OF BRASSINOLIDE ON SOME GROWTH TRAITS AND BIOLOGICAL YIELD OF BREAD WHEAT - J. B, Sura; Al-Hilfy, I. H. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
A field experiment was conducted at the experimental farm, Dept. of Field Crop, Coll. of Agriculture of Engineering Sciences, University of  Baghdad, Al-Jadiriya, Iraq during the winter seasons of 2018-2019 and 2019-2020, to study the effect of brassinolide on some vegetative growth traits of  the bread wheat Triticum aestivum L. variety Rasheed by determining the best soaking periods and the spraying stage to production efficiency. A split plot arrangements were carried out according to RCBD design with three replicates, where the main plots contained three soaking periods of brassinolide (concentration 1 mg L-1 ) 6,12,18 hours, as well as comparison of 18hour distilled water and dry seeds. While the sub plots contained three spraying stages the same of brassinolide concentration (S1: tillering + elongation stage, S2: booting + 100% anthesis stage, S3:100% anthesis + grain formation stage) and tap water was sprayed on plants as control treatment. The results showed that soaking wheat seeds with 12 hours of brassinolide gave highest means for growth traits and biological yield 13.76 and 13.90 Mg ha-1 for both seasons. In addition, the results showed that the spraying stage (tillering + elongation) recorded highest averages in the studies traits above for the both seasons. The interaction between two factors was significant in most studied traits. Therefore we recommend soaking of wheat seeds 12 hour with brassinolide and sprayed with the stage of )tillering + elongation( to obtain the highest vegetative growth and biological yield.